Stigma Sosial Terhadap Anak Pelaku Tindak Pidana Dalam Kebijakan Non Pemenjaraan di Kota Tual - Andhika Khaqiqi; Husni (Cendekia : Jurnal Hukum, Sosial dan Humaniora, 2026)
The phenomenon of social stigma toward children who have been involved in criminal offenses continues to persist despite the implementation of non-custodial policies within the juvenile justice system. Children who resolve their cases through diversion or community-based supervision outside correctional institutions frequently still receive negative labels, encounter social rejection, and face limitations in educational and community interactions. This situation reveals a gap between the rehabilitative orientation of legal policies and the social reality that continues to reproduce exclusion. This study aims to analyze the forms of social stigma, examine their impact on children’s psychological and social development, and evaluate the relevance of non-custodial policies in supporting reintegration. The research adopts a qualitative approach through a literature review and descriptive analysis, drawing on stigma theory and social labeling perspectives developed by Erving Goffman. The findings indicate that the effectiveness of non-custodial policies is not solely determined by formal legal mechanisms, but is also shaped by social acceptance, power relations at the community level, and family support. Without systematic destigmatization strategies, such policies risk shifting punishment from the legal domain to the social sphere. Therefore, public education, strengthened family roles, and cross-sector collaboration are essential to promote sustainable social reintegration.